Hematologic profile of Amazon river dolphins Inia geoffrensis and its variation during acute capture stress - Mello, Daniela Magalhães Drummond de; Silva, Vera Maria Ferreira da (PLoS ONE, 2019)
Hematological values are of primary importance when investigating the health and physiological status of populations as they reflect the biological equilibrium of aquatic ecosystems. The objectives of this study are to produce baseline values for hematological parameters of the Amazon River dolphin (Inia geoffrensis), as well as to investigate significant variations according to sex, age, reproductive status and stress level. One-hundred-and-ten dolphins from Mamirauá Sustainable Development Reserve (3°3'S, 64°51'W), Central Amazon, Brazil, were live captured and sampled in November 2004 and 2005. Further, the means, standard deviations, minimum and maximum values and reference values (90% CI) were calculated. Correlations were performed to assess the relationships among blood values and cardiac rate (CR), respiratory frequency (RF), handling time and level of stress. No significant differences were found between sexes. Also, no differences occurred among pregnant and non-pregnant females, pregnant females and adult males or non-pregnant females and adult males. Calves had a higher white blood cell (WBC) count, and the neutrophil and lymphocyte absolute counts were significantly higher in calves than adults. The level of stress determined by empirical observation positively correlated with the WBC, neutrophil, lymphocyte and monocyte absolute counts and CR and RF. It was found that less stressed animals tend to present lower platelet counts and lower CR. The handling time of the dolphins was positively correlated with hematocrit (Hct), red blood cells (RBC) and Hb level. The hematological and physiological parameters varied according to time of handling and proved to be a good bioindicator of acute stress in Amazon River dolphins. The data provided here can complement long-term monitoring and identify the early warning indicators of health problems at the population level. © 2019 Mello, da Silva. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Hemoglobin; Acute Stress; Adult; Age Distribution; Amazonas; Animals Capture; Animals Cell; Animals Experiment; Animals Trapping; Biological Variation; Blood Examination; Breathing Rate; Calf (mammal); Controlled Study; Erythrocyte Count; Female; Heart Rate; Hematocrit; Hematological Parameters; Hemoglobin Blood Level; Inia Geoffrensis; Leukocyte Count; Lymphocyte Count; Male; Monocyte Count; Neutrophil Count; Nonhuman; Platelet Count; Population Research; Pregnancy; Reference Value; Reproduction; River; Sampling; Sex Difference; Sustainable Development; Time; Toothed Whale; Animals; Blood; Ecosystem; Stress, Physiological; Physiology; Toothed Whale; Animalss; Dolphins; Ecosystem; Female; Heart Rate; Hematocrit; Leukocyte Count; Male; Respiratory Rate; Stress, Physiological